EFFECT OF KIMCHI INTAKE ON LIPID PROFILES AND BLOOD PRESSURE - Hyun Ju Kim; Ji-Sook Han; Eung-Soo Han; Yeong-Ok Song (Kidney Research and Clinical Practice, 2012)
Kimchi is a Korean fermented vegetable and has recognized as a healthy food. Some interventional studies have reported an inverse association between kimchi intake and higher lipid levels in healthy and obese people. However, kimchi intake and hypertention were still uncertain. This study is carried out to investigate whether the serum lipid profiles and blood pressure would be influenced by the amount of kimchi intake. Design for the clinical study by controlling the meal consumption and physical activity of the subjects for 7 days was approved by IRB at P Hospital (No.2011075). For the study, 100 volunteers assigned into 2 groups, low (15 g/day, n=50) and high kimchi intake group (210 g/day, n=50), temporarily stayed together at the dormitory during the 7-day experimental period. Three meals with different amount of kimchi were provided and subjects were asked to maintain the normal physical activity as usual. Significant decrease in the concentration of fasting blood glucose, TG, total-C, and LDL-C for the both group was observed after 7 days of kimchi intake regardless of amount of kimchi intake. Only FBG suppression effect was significantly different (p<0.01). Furthermore, people with hypercholesterolemia (≤19 mg/dL) showed greater improvements in total cholesterol levels in high kimchi intake group. One notable finding in this study was that urinary Na excretion for the high kimchi intake group was significantly increased (p<0.05). There was no significant difference in the BP reductions by kimchi intake. Higher intake of kimchi appears to be a modest beneficial effect to lipid lowering, without any effect on blood pressure in spite of increased sodium excretion. Long-term study should be clarified whether kimchi intake associated with hypertension.